2005
DOI: 10.1177/1096348004270753
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Study of Transfer of Training of Student Employees in a Service Industry

Abstract: It is estimated that organizations spend $200 billion annually on their workforce training.The focus of this qualitative exploratory study was to use Baldwin and Ford's transfer of training model to explore which elements in the model would be perceived as most relevant by student front-line employees for transfer of training, which requires the transfer of information from trainer to trainee. Three focus groups made up of student workers from several dining service units on a university campus were used. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 45 publications
1
32
0
9
Order By: Relevance
“…Bates [28] stated that for transfer to occur, the goals and materials for learning should be content valid. The last decade has proven that the content relevance is correlating with transfer outcomes [14] [29] [30]. Consistent with previous study done by Axtell et al [26], found that content validity was highly correlated with transfer.…”
Section: Learning Designsupporting
confidence: 81%
“…Bates [28] stated that for transfer to occur, the goals and materials for learning should be content valid. The last decade has proven that the content relevance is correlating with transfer outcomes [14] [29] [30]. Consistent with previous study done by Axtell et al [26], found that content validity was highly correlated with transfer.…”
Section: Learning Designsupporting
confidence: 81%
“…As percepções das participantes sobre o desenvolvimento dos atendimentos segundo o modelo de grupoterapia cognitivo-comportamental para crianças e adolescentes vítimas de violência sexual constituem-se como um aspecto relevante ao impacto da capacitação e à transferência de aprendizagem (Lim & Johnson, 2002;Rodríguez & Gregory, 2005). Elas afirmaram que o modelo de grupoterapia cognitivo-comportamental constitui-se como uma intervenção efetiva ao atendimento de crianças e adolescentes vítimas de violência sexual.…”
Section: Discussionunclassified
“…Evidências têm demonstrado que as reações dos participantes à capacitação podem influenciar os índices de impacto e transferência de aprendizagem (Abbad, Borges-Andrade, & Sallorenzo, 2004;Cheng & Ho, 2001;Grossman & Salas, 2011;Lim & Johnson, 2002;Rodríguez & Gregory, 2005). Dentre os elementos que constituem as reações dos participantes à capacitação destacam-se as percepções do participante sobre a relevância dos conteúdos e técnicas trabalhados e a possibilidade de utilizá-los em seu contexto laboral (Abbad et al, 2004;Rodríguez & Gregory, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Analizando la dimensión de la formación, distintos autores encuentran relaciones entre la transferencia y el factor orientación a las necesidades del puesto de trabajo (e.g., Baldwin y Ford, 1988;Bates et al, 2007;Paas y Van Merriënboer, 1994;Pérez, 2008;Rodriguez, 2005;. Además de los factores mencionados se han encontrado relaciones entre variables que no aparecen recogidas en el modelo de Pineda et al (2013), como son el factor generación de una comunidad o red de profesionales, referido al grado en que los participantes generan una red profesional para comentar, colaborar o compartir ideas relacionadas con la formación, la organización o su práctica profesional (e.g., Boud y Middleton, 2003;Ingvarson, Meiers y Beavis, 2005).…”
Section: Introductionunclassified